Geolinguistics of the evidential future tense in Romance languages at the beginning of the 20th century - Lara Bermejo, Víctor (2021)
The morphological future tense in the Romance languages can express time, modality and evidentiality. The literature states that almost all varieties use this tense to denote inference or conjecture, but the data researchers use is based on their own introspection, as well as on literary texts. In this paper, I attempt to give an account of the validity of the morphological future tense at the dialectal level in all Romance languages at the beginning of the 20th century in order to determine whether its conjectural value was indeed possible at that time and to what extent it can be concluded that Romance languages possess morphological evidentiality.